Preparation and swelling study of CMC hydrogel as potential superabsorbent - Che Nan, Nur Fitrah; Zainuddin, Norhazlin; Ahmad @ Ayob, Mansor (Universiti Putra Malaysia Press, 2019)
Carboxymethylcellulose (CMC) is a water-soluble polymer, which is widely used in various fields such as food additives, textiles, pharmaceuticals and cosmetics. In this study, hydrogel was prepared from CMC by using calcium chloride as a crosslinking agent. Optimization of the reaction was done through investigation of four different parameters which had different percentage of CMC (w/v), percentage of calcium chloride (w/v), reaction time and temperature. The gel content and swelling properties of the CMC hydrogel were studied. The highest gel content was 85.33% at 7% of CMC (w/v) with 2% of calcium chloride (w/v) in 24 hours reaction time at room temperature. The gel content increased with the increasing concentration of CMC and CaCl2. This was due to the higher number of functional groups of COO- that were available in more concentrated CMC which could crosslink with CaCl2 to give higher gel content. Increasing the percentage of CaCl2 will increase the electrostatic attraction between anionic charges of polymer chains and multivalent cation (Ca2+) that leads to increase in ionic crosslinking of CMC. The swelling properties of CMC hydrogel showed that the optimum degree of swelling was 45.33 (g/g). The swelling capacity of the hydrogel in water decreased with the increase of the gel content of CMC hydrogel. This could be due to the increase in the degree of crosslinking of the CMC hydrogel.